Beyond Maps: How Web-GIS InaRisk and Group Investigation Redefine Disaster Mitigation Education - Diva Prameswari Nirmala; Alfyananda Kurnia Putra; Uuriintuya Dembereldorj; Ella Pertiwi (Future Space: Studies in Geo-Education, 2025)
This research aims to determine the influence of the Web-GIS InaRisk-assisted group investigation model on students' critical thinking skills, as viewed through their learning motivation, in disaster mitigation subjects. The method employed in this research is quantitative with a quasi-experimental research design. The research subjects for this experiment are students of class XI IPS 2 and XI IPS 3 of MAN Kota Batu, divided into experimental and control groups. Research instruments used include essay questions and questionnaires to measure students' critical thinking skills and learning motivation. Data analysis methods used to determine the influence of the Web-GIS InaRisk-assisted group investigation model on critical thinking skills, as viewed through learning motivation in this research, are Mann Whitney and Kruskal Wallis tests. This study was conducted from February to March 2024 and obtained two findings. The first finding is that the Web-GIS Inarisk assisted group investigation model affects critical thinking skills because hypothesis 1 test is Sig. 0.04 and the second finding is that the Web-GIS Inarisk assisted group investigation model affects critical thinking skills in terms of student learning motivation, because hypothesis 2 test is Sig. 0.00.